Prostanoid Release from Ex Vivo Perfused Canine Arteries and Veins: Effects of Prolonged Perfusion, Intermittent Perfusion, as well as Exposure to Exogenous Arachidonic Acid, Thrombin and Bradykinin - Brunkwall, Jan S; Stanley, James C; Kresowik, Timothy F; Graham, Linda M; Burkel, William E; Bergqvist, David (Thrombosis and Haemostasis, 1989)
Regulation of prostanoid release from ex vivo perfused vessel segments is not fully understood. A series of perfusion experiments were performed with canine arteries and veins to define certain regulatory phenomena. Arteries were perfused with pulsatile flow of 90 ml/min at a pressure of 100 mmHg, and veins with nonpulsatile flow of 90 ml/min at a pressure of 7 mmHg. Segments were perfused with Hanks' balanced salt solution for five 15-min periods with the perfusate exchanged after each study period. With onset of perfusion, there was an initial burst of prostacyclin release to 127 ± 40 pg/mm2, declining to 32 ± 10 pg/mm2 after 60 minutes (p <0.005). If perfusion continued for 5.5 hours, there was a stable release period between 1 and 3 hours, followed by a very slow decline. At that time addition of arachidonic acid (AA) increased prostacyclin release six-fold (p <0.01). Vessels perfused for 1 hour and then rested for another hour, responded to reperfusion at the second onset of flow with a two-fold increase in prostacyclin release (p <0.01). Vessels perfused with thrombin, bradykinin or A A (either added to each perfusate or only to the last perfusate) exhibited greater prostacyclin release than did control segments. Release of thromboxane steadily declined with time in all parts of the study, and only increased with the addition of A A to the perfusate. These data indicate that vessel segments subjected to ex vivo perfusion do not maximally utilize enzyme systems responsible for prostanoid production, and after 1 hour perfusion have not depleted their phospholipids, and maintain functioning levels of phospholipase and cyclooxygenase activity. This perfusion model allows for the study of prostacyclin and thromboxane release from arteries and veins and their response to various drugs and other stimuli.
Keywords: Vessel wall; Prostanoid release; Arachidonic acid; Thrombin; Bradykinin